2021
DOI: 10.2169/internalmedicine.6206-20
|View full text |Cite
|
Sign up to set email alerts
|

Negative-pressure pulmonary Hemorrhaging Due to Severe Obstructive Sleep Apnea

Abstract: A 24-year-old man with a history of bloody sputum for 6 months was referred to our hospital with suspected alveolar hemorrhaging due to vasculitis. Chest computed tomography showed ground-glass opacities in both lungs, and an examination of his bronchoalveolar lavage fluid showed alveolar hemorrhaging. However, no evidence of vasculitis was found, and subsequent polysomnographic testing confirmed that he had severe obstructive sleep apnea (OSA). Since the alveolar hemorrhaging improved after the initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…There have been several reports of NPPH in the perioperative period, triggered by laryngospasm after extubation 3) . In Japan, only a few other cases of choking due to food aspiration and sleep apnea have been reported 6,7) . Table 2 summarizes the case reports of NPPH in Japan according to noninvasive etiology.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of NPPH in the perioperative period, triggered by laryngospasm after extubation 3) . In Japan, only a few other cases of choking due to food aspiration and sleep apnea have been reported 6,7) . Table 2 summarizes the case reports of NPPH in Japan according to noninvasive etiology.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly considered that the permeability of pulmonary capillaries increases under the condition of negative thoracic pressure ( 41 ). In general, when pulmonary vascular compliance is low, an increase in pulmonary blood volume can alter membrane permeability and even disrupt membrane integrity, which ultimately leads to leakage of body fluids and blood cells into the alveoli ( 20 , 41 ). This damaging effect has been demonstrated both experimentally and clinically ( 1 , 42 , 43 ).…”
Section: Pathogenesis and Pathophysiological Featuresmentioning
confidence: 99%
“…Reports on mortality also vary. The mortality rate of NPPE has previously been described as 11 to 40%, with a more recent literature review showing a mortality rate of only 2% (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A recent systematic review of NPPE in adult ear, nose and throat (ENT) surgery reported a mortality rate of 5% and identified age and ICU admission as the main risks for increased mortality (3).…”
Section: Introductionmentioning
confidence: 99%
“…Auch bei der obstruktiven Schlafapnoe werden in Einzelberichten Fälle von Patienten mit nächtlichem Lungenödem und Hämoptysen beschrieben [9][10][11][12][13]. Kuramoto et al berichten von einem 24-jährigen athletischen männlichen Patienten mit seit etwa 6 Monaten bestehendem blutigen Sputum (morgendlich nach dem Aufstehen), bei dem eine umfangreiche Umfelddiagnostik keine richtungsweisende Erklärung ergeben hat [9]. Nach Durchführung einer Polysomnografie konnte eine schwergradige obstruktive Schlafapnoe mit einem AHI von 93,8/h festgestellt werden.…”
Section: Introductionunclassified